Construction of molecular structure model of bituminous coal and study on adsorption characteristics of C2H4 and C2H2 - Ji Wu; Zongxiang Li; Shuoran Huang; Cong Ding (Scientific Reports)
Abstract The abandoned coal in goaf will adsorb the gases ethylene (C2H4) and acetylene (C2H2) produced by coal oxidation, which makes the concentration data of the indicator gas inaccurate. Therefore, the adsorption law of coal and C2H4 and C2H2 gas is explored. The macromolecular structure model of coal was established and optimized by simulation, and the gas adsorption process was simulated by means of grand canonical Monte Carlo method. The adsorption quantities and adsorption sites of single component and binary component gases C2H4 and C2H2 in coal under different temperatures and pressures were analyzed. The results show that the molecular formula of S7 and W12 coal samples is C136H92O30N2S and C129H87O28N2S, respectively. When C2H4 and C2H2 are adsorbed at the same temperature, the adsorption pressure is positively correlated with the adsorption capacity, and the adsorption capacity increases rapidly with the increase of pressure, and then tends to be flat. With the same pressure, the adsorption capacity of C2H4 and C2H2 is unfavorable with the increase of temperature. The adsorption sites of C2H2 are more than those of C2H4. When C2H4 and C2H2 gas are used as indicator gases alone, they will be adsorbed by the left coal in the goaf, which makes the on-site monitoring gas concentration data inaccurate, resulting in the delay of the early warning time to a certain extent.